2022
DOI: 10.3892/etm.2022.11598
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 expression alleviates microglia activation‑induced dopaminergic neuron injury through the mitochondrial pathway

Abstract: The mitochondrial protein sirtuin 3 (SIRT3) can counteract cell damage caused by oxidative stress and inflammation, and contribute to cell survival primarily by improving mitochondrial function. However, the effects of SIRT3 in dopaminergic neuronal cells (DACs) remain unclear. In our previous studies, microglia activation-associated cytotoxicity was observed to promote the apoptosis of DACs, along with the decrease of SIRT3 expression. The aim of the present study was to explore the potential neuroprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…37 Moreover, knockdown of Sirt3 using siRNA in microglia further exacerbates the cytotoxicity mediated by microglial activation, including increased accumulation of ROS and enhanced apoptosis. 38 Based on these studies, we overexpressed Sirt3 by lentiviral transfection and we found that apoptosis was inhibited in the high glucose group. This is consistent with the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, knockdown of Sirt3 using siRNA in microglia further exacerbates the cytotoxicity mediated by microglial activation, including increased accumulation of ROS and enhanced apoptosis. 38 Based on these studies, we overexpressed Sirt3 by lentiviral transfection and we found that apoptosis was inhibited in the high glucose group. This is consistent with the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also suggested that the accumulation of α‐syn in PD inhibits mitochondrial function by affecting the level of mitochondrial sirtuin 3 protein, an NAD + ‐dependent deacetylase that regulates the acetylation/deacetylation level of complex I 201 . The sirtuin 3 in mitochondria has been proven to prevent dopaminergic neuron loss in a rodent model of PD 202 . This indicates that dysfunction of complex I plays an important role in mediating PD pathology.…”
Section: Iron Metabolism In Brain Diseasesmentioning
confidence: 99%
“… 201 The sirtuin 3 in mitochondria has been proven to prevent dopaminergic neuron loss in a rodent model of PD. 202 This indicates that dysfunction of complex I plays an important role in mediating PD pathology. In addition, complex II–IV are also inhibited to varying degrees in PD, suggesting impaired mitochondrial oxidative respiration in PD.…”
Section: Iron Metabolism In Brain Diseasesmentioning
confidence: 99%
“…Microglial activation-induced oxidative stress injury on NSCs has been shown to be prevented by SIRT3 in a coculture system [ 113 ]. Microglial activation-induced cytotoxicity in dopaminergic neuronal cells is alleviated by Sirt3 overexpression while Sirt3 gene aggravates neurotoxicity [ 114 ]. HIV TAT protein induces senescence in mouse primary microglial cells with downregulation of SIRT3 while overexpression of Sirt3 in these cells reverses this senescence-like phenotype [ 115 ].…”
Section: Sirt3 Downregulation In Disease Conditionsmentioning
confidence: 99%
“…Another study reported that SIRT3 overexpression protects rotenone-treated SH-SY5Y cells by decreasing apoptosis and ROS and by preventing α-synuclein accumulation whereas Sirt3 silencing results in increased cell apoptosis, reduced SOD and GSH, and increased accumulation of α-synuclein [ 135 ]. The activated BV2 cells, a mouse microglial cell line, have been shown to promote apoptosis and decrease Sirt3 expression in MN9D cells, mouse midbrain dopaminergic cell line [ 136 ] whereas Sirt3 expression in MN9D cells shows a neuroprotective effect against microglia activation-induced neuronal injury, by modulating mitophagy-NLRP3 inflammasome pathway [ 114 ].…”
Section: Sirt3 Downregulation In Disease Conditionsmentioning
confidence: 99%